2006
DOI: 10.5962/bhl.part.80357
|View full text |Cite
|
Sign up to set email alerts
|

Identification biométrique des deux espèces sympatriques de souris Mus musculus domesticus et Mus spretus en Kabylie du Djurdjura (Algérie)

Abstract: Identification biométrique des deux espèces sympatriques de souris Mus musculus domesticus et Mus spretus en Kabylie du Djurdjura

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Badiaf et al (2013) caught 6 specimens in Djanet region; an extreme southeast of Algeria with an altitude of 1094 MASL. Khammes et al (2006) found this species in the Kabylie of Djurdjura and in Morocco, Stoetzel et al (2012) and Denys et al (2015) reported the presence of this rodent respectively at 9% and 5%. In this study, we did not find the Algerian mouse Mus spretus Lataste, 1883, its absence can be conditioned by climatic circumstances and altitude.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Badiaf et al (2013) caught 6 specimens in Djanet region; an extreme southeast of Algeria with an altitude of 1094 MASL. Khammes et al (2006) found this species in the Kabylie of Djurdjura and in Morocco, Stoetzel et al (2012) and Denys et al (2015) reported the presence of this rodent respectively at 9% and 5%. In this study, we did not find the Algerian mouse Mus spretus Lataste, 1883, its absence can be conditioned by climatic circumstances and altitude.…”
Section: Discussionmentioning
confidence: 93%
“…Among the previous works carried out on rodents inventories in Algeria we quote: Kowalski & Rzebik-Kowalska (1991), Belabbas & Butet (1994), Hamdine (2000) and Hamdine et al (2006), Khammes et al (2006) and Khammes & Aulagnier (2007). More recently, the works of Adamou-Djerbaoui et al (2010, 2011, 2013, Bachar & Belhamra (2012), Souttou et al (2012), Beddiaf et al (2013) and Hadjoudj et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore likely that this habitat type is able to provide an adequate supply of trophic resources different from acorns, such as fruits and seeds, as already suggested by our former work [30] in the same study area. In fact, wood mice are characterized by a marked foraging plasticity that allows them to change their diet based on the most abundant available foods [63][64][65]. In a previous investigation in our study area, we observed that wood mice in autumn consumed different food items from several shrub species, in addition to acorns [30].…”
Section: Discussionmentioning
confidence: 57%
“…However, conifer plantations do not produce acorns [30], which are among the main trophic resources for mice found in oak forests [59,60], especially during cold months [14,[59][60][61][62][63]. Nonetheless, we found wood mice to be more abundant in conifer plantations in the cold season than in the hot one.…”
Section: Discussionmentioning
confidence: 72%